Heterotrophic carbon gain by the root hemiparasites, Rhinanthus minor and Euphrasia rostkoviana (Orobanchaceae) - Tesitel, Jakub; Plavcová, Lenka; Cameron, Duncan D (Planta, 2010)
Hemiparasitic plants gain virtually all mineral nutrients and water from their host plant whilst organic carbon is provided, at least in part, by their own photosynthetic activity, although their rates of assimilation are substantially lower than that found in non-parasitic plants. Hence, hemiparasites must gain at least some of their organic carbon heterotrophically from the host plant. Despite this, heterotrophic carbon gain by root hemiparasites has been investigated only for a few genera. We investigated heterotrophic carbon gain by two root hemiparasites, Rhinanthus minor L. and Euphrasia rostkoviana Hayne (Orobanchaceae), using natural abundance stable isotope (delta(13)C) profiles of both parasites attached to C(3) (wheat) and C(4) (maize) hosts coupled to a linear two-source isotope-mixing model to estimate the percentage of carbon in the parasite that was derived from the host. Both R. minor and E. rostkoviana attached to maize hosts were significantly more enriched in (13)C than those attached to wheat hosts with R. minor becoming more enriched in (13)C than E. rostkoviana. The natural abundance (13)C profiles of both parasites were not significantly different from their wheat hosts, but were less enriched in (13)C than maize hosts. Using a linear two-source isotope-mixing model, we estimated that R. minor and E. rostkoviana adult plants derive c. 50 and 25% of their carbon from their hosts, respectively. In light of these results, we hypothesise that repeatedly observed negative effect of competition for light on hemiparasites acts predominantly in early ontogenetic stages when parasites grow unattached or the abstraction of host nutrients is less effective.
Keywords: Photosynthesis; Zea mays; Orobanchaceae; Carbon Isotopes; Euphrasia; Heterotrophic Processes; Plantago; Host-Parasite Interactions; kukuřice setá; pšenice; biomasa; Carbon; kořeny rostlin; izotopy uhlíku; Triticum; Biomass; uhlík; Plant Roots; fotosyntéza; interakce hostitele a parazita; heterotrofní procesy